TI_GERICHTE 52.2009.339 vom 18. März 2010 , Impianto pubblicitario. Potere d'intervento dell'autorità di vigilanza - TI Tribunale d'appello (2010)
Impianto pubblicitario. Potere d'intervento dell'autorità di vigilanza